Different sleep pattern in over-weight/obese women with polycystic ovary syndrome - Oberg, Emma; Blomberg, Liselotte; Åkerstedt, Torbjörn; Hirschberg, Angelica Lindén (Frontiers in Endocrinology, 2023)
Context: Sleep duration and sleep quality have important health implications although our knowledge of objectively measured sleep variables in women with Polycystic Ovary Syndrome (PCOS) is limited. Objective: To compare sleep variables assessed by actigraphy in over-weight/obese women with PCOS and controls, and to assess sleep variables after behavioral modification intervention in comparison with minimal intervention in a randomized trial. Design: Randomized controlled trial, and a control group. Setting: Outpatient gynecological clinic at a university hospital in Sweden. Participants: 39 women fulfilling all Rotterdam PCOS criteria, randomized to behavioral modification intervention or minimal intervention and 21 controls with no other metabolic disease, all aged 18‐40 years with a BMI ≥ 27 kg/m2. Intervention: A four-month behavioral modification intervention including weekly group meetings focusing on behavioral and healthy lifestyle aspects. Minimal intervention reflecting standard care. Main outcome measure: Sleep durations and sleep efficiency assessed by actigraphy. Results: Compared to the control group, women with PCOS had significantly shorter time in bed (501 vs 548 min, p= 0.049), sleep time over 24 hours (448 vs 567 min, p=0.005) and sleep time at night (434 vs 511 min, p=0.002), poorer sleep efficiency (87 vs 93 %, p<0.001), and longer wakefulness after sleep onset (64 vs 38 min, p<0.001). However, total sleep time at night for women with PCOS (7.2hrs) was within the normal range. Following behavioral modification intervention, the reduction from baseline in sleep over 24 hours and in the daytime sleep were significant compared to the minimal intervention group (78 min, p=0.009 and 43 min, p=0.003 respectively). Conclusions: We found over-weight/obese women with PCOS to have normal sleep duration, but worse sleep efficiency than controls. Behavioral modification intervention seems to reduce the amount of daytime sleep, suggesting improved sleep behavior. Clinical trials registration number: ISRCTN48947168, URL: https://doi.org/10.1186/ISRCTN48947168